South Korean Modern Culture in the Drama Series â€œJust One Biteâ€ (Semiotics Analysis by Charles Sanders Peirce) - Nurul Fikriyyah Taqwa; Ikhwan M Said; Hamzah Machmoed; Dafirah Dafirah; Fadhliyah Rahmah Muin (Institut Agama Islam Negeri Palopo, 2023)
The purpose of this study is to analyze and describe the modern cultural values of South Korea which are represented in the drama series